Fabrication and measurement of nanomechanical resonators - Cousins, Richard (2017)
Over the past years there has been great progression in the field of micro- and nanomechanics with devices with higher and higher Q factors being created. This has been made possible thanks to a combination of advances in fabrication techniques and an increase in understanding as to what causes dissipation in nanometre scale structures. This understanding of dissipation mechanisms is still incomplete however. While lots of work has been done investigating mechanisms such as thermoelastic dissipation and dissipation due to two level systems (TLS) within the standard tunnelling model (STM) a full understanding has not been forthcoming. The increase in the quality of nanomechanical systems has allowed them to be coupled to optical or microwave cavities allowing the position of the mechanical system to be measured with near quantum limited accuracy. This thesis looks at both these streams of research within nanomechanics. It looks at the fabrication of silicon nitride torsional resonators that can have either their flexural or torsional modes preferentially actuated via a piezoelectric drive. It was found for a single paddle resonator that the room temperature Q factor of the flexural mode was 2870±70 and for the torsional mode was 5050±220. It was shown that while thermoelastic damping was reduced in the torsional mode it was still present meaning that we could not use the model for a simple beam to describe thermoelastic damping for a paddle resonator. The properties of an nanomechanical beam fabricated from a single crystal of aluminium were also investigated. It was found that at 1.5 K it had an unloaded Q factor of 36900 which is at least 2 times larger then any other group has reported. We also used our knowledge of high stress silicon nitride membranes to design a system that could couple an aluminium on silicon nitride membrane to a LCR circuit. Calculations show that this would have a coupling constant, g, of over 1000 putting it well within the regime where ground state cooling and quantum limited measurements are possible.